Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphar.2018.01551
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase for Renal Health

Abstract: A soluble epoxide hydrolase (sEH) mediates the metabolism of epoxy fatty acids to form the corresponding vicinal diols, which are usually inactive or less active than the epoxide substrates. The sEH enzyme presents in many organs, including but not limited to the liver, heart, spleen, lung, and kidney. Here we summarized the changes in the expression and activity of sEH in multiple renal diseases, such as acute kidney injury (AKI), diabetic nephrology (DN), chronic kidney diseases (CKD), hypertension-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 107 publications
(154 reference statements)
1
26
0
Order By: Relevance
“…Renal sEH is up-regulated in several hypertensive models, and inhibition of sEH lowers their BP (Liu, 2018), similar to our results in SKI mice. In this present report we have not investigated how SERCA2 may regulate sEH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Renal sEH is up-regulated in several hypertensive models, and inhibition of sEH lowers their BP (Liu, 2018), similar to our results in SKI mice. In this present report we have not investigated how SERCA2 may regulate sEH.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with WT mice, the sEH of SKI mice increased and D 1 receptors decreased at the level of mRNA ( Figure S3), which were further supported at the level of protein in both renal cortex and primary RPT cells (Figure 4). sEH was mainly located in the RPT of kidney ( Figure S4; Liu, 2018) and this enzyme metabolizes epoxyeicosatrienoic acids to less active dihydroxyeicosatrienoic acids (He, Wang, Zhu, & Ai, 2016), and thus inhibits sodium excretion by enhancing the activity of Na + /K + -ATPase in RPT (Dos Santos, Dahly-Vernon, Hoagland, & Roman, 2004;Imig, 2000;Imig, 2004). On the contrary, activation of D 1 receptors promotes sodium excretion by inhibiting Na + /K + -ATPase in RPT (Zeng & Jose, 2011;Harris & Zhang, 2012).…”
Section: Inactivation Of Serca2 C674 Up-regulates the Expression Ofmentioning
confidence: 99%
“…sEH is a cytosolic enzyme that is widely distributed in the liver, heart and kidney, and it plays a pivotal role in the regulation of EET bioavailability 19 . Numerous studies have highlighted the potential benefits of sEH inhibition in the inflammatory response 20 , cardiovascular diseases 21 , non-alcoholic fatty liver 22 and renal disease [23][24][25] . A recent study demonstrated that the sEH inhibitor TUPS mitigated isoproterenol/angiotensin IIinduced cardiac hypertrophy by inhibiting mTOR signaling-mediated autophagy 26 , which indicated that sEH is associated with the regulation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…7 In many experimental studies, it was found that the inhibition of sEH had a renoprotective effect. 16,17 sEH is encoded by EPHX2 gene. 18 A common SNP in the EPHX2 gene is the functional rs751141 G/A polymorphism.…”
Section: Introductionmentioning
confidence: 99%